2014
DOI: 10.3762/bjoc.10.128
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization–endoperoxidation cascade reactions of dienes mediated by a pyrylium photoredox catalyst

Abstract: SummaryTriarylpyrylium salts were employed as single electron photooxidants to catalyze a cyclization–endoperoxidation cascade of dienes. The transformation is presumed to proceed via the intermediacy of diene cation radicals. The nature of the diene component was investigated in this context to determine the structural requirements necessary for successful reactivity. Several unique endoperoxide structures were synthesized in yields up to 79%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…[58] To expand the scope of this reaction, the Nicewicz group developed new conditions based on those of Yoon and Miyashi [59] and aimed to use higher-oxidation-potential olefins through the use of organic photocatalysts (Scheme 42). [57] The mechanism proposed by the authors is similar to that proposed by Yoon on the basis of the results obtained by Miyashi. Nonetheless, the Nicewicz group performed DFT calculations, and the results suggested the formation of a distonic radical cation.…”
Section: Multiple-bond-centered Radical-mediated Reactivitysupporting
confidence: 75%
See 2 more Smart Citations
“…[58] To expand the scope of this reaction, the Nicewicz group developed new conditions based on those of Yoon and Miyashi [59] and aimed to use higher-oxidation-potential olefins through the use of organic photocatalysts (Scheme 42). [57] The mechanism proposed by the authors is similar to that proposed by Yoon on the basis of the results obtained by Miyashi. Nonetheless, the Nicewicz group performed DFT calculations, and the results suggested the formation of a distonic radical cation.…”
Section: Multiple-bond-centered Radical-mediated Reactivitysupporting
confidence: 75%
“…Nicewicz and colleagues later detailed this step on the basis of the formation enthalpy along with spin-density calculations. [57] Indeed, they suggest the effective formation of the distonic radical cation species 204, which is intercepted by O 2 to form 205. This intermediate is then reduced by 1 equiv.…”
Section: Multiple-bond-centered Radical-mediated Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the scope of the aerobic [2+2+2] cycloaddition was significantly extended by Yoon and co‐workers to include less electron‐rich bis(styrene) substrates using Ru(bpz) 3 2+ as an efficient photocatalyst . Most recently, and most relevantly to this work, Gesmundo and Nicewicz showed that the use of triarylpyrylium salts as organic photocatalysts allowed the aerobic [2+2+2] cycloaddition of dienes bearing one styrene and one aliphatic alkene (Scheme ) …”
Section: Methodsmentioning
confidence: 99%
“…[12] Most recently,a nd most relevantly to this work, Gesmundo and Nicewicz showed that the use of triarylpyrylium salts as organic photocatalysts allowed the aerobic [2+ +2+ +2] cycloaddition of dienes bearing one styrene and one aliphatic alkene (Scheme 2). [13] Our biomimetic synthesis of nyingchinoids A, B, and Dis outlined in Scheme 3. Racemic chromene 4 was first synthesised in one step by condensation of orcinol with citral according to ak nown procedure.…”
mentioning
confidence: 99%